PENINGKATAN KOMPETENSI GURU PAUD MELALUI PELATIHAN PENGAJARAN AL-QUR’AN DASAR METODE AL-BARQY - Farida, Neng Awalia; Afriliani, Ajeng Teni Nur; Muti, Irma; Grahani, Puri; Rahayu, Nisa (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
This community service program aims to improve the competence of early childhood education (PAUD) teachers in teaching basic Quranic recitation to early childhood through training in the use of the Al-Barqy method. The reason for this activity is that many PAUD teachers are still confused and have not yet mastered effective Quranic teaching strategies, resulting in many young children still not optimally recognizing the Hijaiyah letters and basic Quranic recitation. The method used in this study is descriptive qualitative, with data collection through observation, interviews, and documentation. The number of participants in this activity was 40 people and took place at the Al-Hidayah Ciaul Mosque Hall, Sukabumi City. The implementation process was carried out in three stages: preparation, implementation, and reflection-evaluation. The results showed that through this activity, many teachers provided positive responses, stating that teachers gained new understanding, improved teaching skills, and increased confidence in delivering Quranic material. Thus, this training not only positively impacted teacher competence but also contributed to strengthening Islamic religious education in PAUD and fostering children's love of the Quran from an early age.